Retroperitoneal paraganglioma in a young patient presenting with hypertensive crisis and transient loss of sight; a rare case report and literature review. (December 2022) - Mulenga, Kasonde; Kazuma, Seke Manase Ephraim; Nonde, James; Mbewe, Chitani; Volodymyr, Petrenko; Musowoya, Joseph
Abstract: Introduction: Catecholamine secreting tumors are a rare type of neuroendocrine tumors whose embryological origin is neural crest cells. 80 % to 90 % arise from the chromaffin cells of adrenal medulla while 10 % to 20 % arise from sympathetic and parasympathetic ganglia. Paragangliomas can be symptomatic due to excess catecholamine secretion or can be asymptomatic. Definitive treatment of paragangliomas is surgical resection. Case: A 16 yr old male who presented with right iliac fossa pain and hypertension associated with headache and transient loss of sight. Contrasted CT scan of the abdomen revealed a para-aortic retroperitoneal mass, 24 h urine Normetanephrines were significantly elevated. Pre-operative patient preparation included administration of alpha blockers then later beta blockers with adequate hydration. Intra operative blood pressure elevation during tumor manipulation managed with intravenous beta blockers. Post operatively patient required no inotropic support or anti hypertensives. Histopathology revealed features suggestive of a paraganglioma and immunohistochemistry s100 (+) Chromogranin A (+). Discussion: Functional paragangliomas are manifested by symptoms that result from catecholamine hypersecretion. Biochemical confirmation and functional localization of the tumors is recommended. Definitive management is surgical resection with a pre requisite of adequate patient preparation which includes blood pressure control and volume replacement. Conclusion: Tumor localisation and adequate patient preparation with alpha blockers and adequate hydration is an important prerequisite to surgical resection. Highlights: Retroperitoneal Paraganglioma Catecholamine secreting tumor arise from cells of neuro crest origin Hypertensive crisis Organ of Zuckerkandl 24-hour urine metanephrines and nor-metanephrines